HOW DOES FINANCIAL INCLUSION AFFECT HUMAN DEVELOPMENT? EVIDENCE FROM ALGERIA - Nid Safa; Heriat Bouthaina (International Journal of Innovative Technologies in Social Science, 2025)
This study explores the relationship between financial inclusion and human development in Algeria from 2004 to 2021, using a composite index of financial inclusion and the Autoregressive Distributed Lag (ARDL) model. The research integrates two dimensions of financial inclusion: access to financial services and usage of financial services, using indicators such as ATMs, bank branches, bank deposits, and domestic credit. The results confirm a long-run cointegration between financial inclusion and human development. In the short run, financial inclusion significantly impacts human development, with a 38.9% adjustment rate towards equilibrium. The findings underscore the vital role of financial inclusion in enhancing human development, with implications for policy aimed at fostering economic growth and improving living standards. The study also emphasizes the importance of strengthening financial systems to maximize these effects.